The Effects of External Jugular Compression Applied during High Intensity Power, Strength and Postural Control Tasks - DiCesare, Christopher A.; Barber Foss, Kim D.; Thomas, Staci; Schneider, Daniel K.; Edwards, Nicholas M.; Myer, Gregory D. (Current Research: Concussion, 2017)
Introduction Current strategies focused on mitigating concussion in sport have demonstrated limited effectiveness. There is a paucity of research on the optimization of intracranial brain dynamics to mitigate concussion; in the present study, we investigate a novel device that provides mild jugular vein compression and may provide adjunctive protection to protect the brain internally from concussive and sub-concussive impacts. The purpose of this study was to assess the tolerance and acceptance of this device in a population of normal, healthy adults undergoing exertion similar to that is experienced while participating in sports-related competition, while monitoring changes in their biomechanical, strength, power, and postural stability capabilities.Material and Methods A total 18 participants (8 females, 10 males) were tested and included in the final analysis. Laboratory data collection consisted of two separate testing sessions for all participants. During the first testing session, participants were tested while wearing either the mild jugular vein compression neck device or a sham arm device (Sham) that was worn on the upper arm and did not alter venous return; participants exchanged devices for the second session. Participants underwent a battery of physical and neurological tests that included three-dimensional (3-D) biomechanical analysis, dynamic postural control testing using a stabilometer, isokinetic strength testing using a dynamometer, and a maximum vertical jump test.Results Evaluation of vital biomechanics, postural control and dynamic stabilization, isokinetic strength, and power in this population showed no statistically significant effect of wearing a mild jugular vein compression neck device compared with a Sham armband.Conclusions The data evaluated in the current project indicate that the device is safe during high intensity and dynamic postural stabilization exercise and does not alter normal physical or neuromuscular capabilities during physical activity.
Keywords: concussion; jugular vein; biomechanics